EFISIENSI SKALA USAHATANI PERKEBUNAN KELAPA SAWIT DAN DISTRIBUSI PENDAPATAN PETANI DI PROPINSI KALIMANTAN TIMUR - Daroni Daroni; Sri Widodo; Dwidjono Hadi Darwanto; Sofyan P Warsito (Agro Ekonomi, 2004)
The objective of this research is to study the farmscale efficiency of oil palm smallholders. In this context it will also be studied the change in shifting cultivation activity and distribution of oil palm farmer income.The research was done in East Kalimantan with samples of 350 farmers by "Stratified Random Sampling" technique. The oil palm development in the East Kalimantan has a high potential to improve its business scale efficiency. In case there will be opportunities to reduce the cost to increase the production with additional input of fertilizer. Another opportunity is expanding farm size of ≥ 2 hectares will give better income rather than <2 hectares. In the same level of the employing input, the oil palm farm 012 hectares will produce higher Fresh Bunches with lower input.The oil-palm farming in the East Kalimantan is indicated by a reversel relationship between size and efficiency. The analyze of results signify that the larger farm have lower productivity. Using the same input or factor of production, however, the oil-palm farm agribusiness with ≥ 2 hectares width will gain higher benefit with lowercost. The production cost 0/the oil-palm operation of the small holders in the East Kalimantan has not gain the level of the technical efficiency as well as the cost efficiency (allocative efficiency). The oil-palm business scale of the small holders indicates that the scale economy in decreasing return to scale.The development of the oil-palm farming of small holders positively affects to reduce the pressure of population on the forest land resource in the shifting cultivatin of 81.46 percent. The income distribution in low in equality. The a Gini Index of 0.196 ( the evently distributed income).It is consistent with the income distribution analysis result based on the land farm size ownership in percentile The economies of scale of the oil-palm small holders will be achieved by the land size of ≥2 hectares. In related the family labors available, the small holders of the East Kalimantan are enable to operate the oil palm plantation of 5.7 hectares per farmer family.